High Performance Computing in Science and Engineering '09: Transactions of the High Performance Computing Center, Stuttgart (HLRS) 2009 - Nagel, Wolfgang E.; Kröner, Dietmar B.; Resch, Michael (Springer-Verlag Berlin Heidelberg, 2010)
Physics -- Numerical Models for Emission Line Nebulae in High Redshift Radio Galaxies -- The SuperN-Project: Current Advances in Understanding Core Collapse Supernovae -- Using Computational Steering to Explore the Parameter Space of Stability in a Suspension -- Solid State Physics -- Adsorption of Cysteine on the Au(110)-surface: A Density Functional Theory Study -- Characterization of Colloidal IV-VI Semiconductor Quantum Dots -- Understanding Long-range Indirect Interactions Between Surface Adsorbed Molecules -- H Carrying Capacity by Considering Charging and Discharging Processes – Case Studies on Small Carbon- and Boron Nitride Nanotubes -- Molecular Dynamics Study of Plastic Deformation of Nanocrystalline Palladium -- Conductance of Correlated Nanostructures -- Chemistry -- How do Eigenfunctions of Douglas-Kroll Operators Behave in the Vicinity of Point-like Nuclei? -- Distributed Memory Parallelization of the Multi-Configuration Time-Dependent Hartree Method -- Development of Models for Large Molecules and Electrolytes in Solution for Process Engineering -- Reacting flows -- Numerical Characterization of a Gas Turbine Model Combustor -- Numerical Investigations of NO-Formation in Scramjet Combustors -- Large-Eddy Simulation of Lean Premixed Flames in a Model Swirl Burner -- Computational Fluid Dynamics -- Higher Order Adaptive and Parallel Simulations Including Dynamic Load Balancing with the Software Package DUNE -- Direct Numerical Simulation of Jet in Crossflow Actuators -- Laminar Heat Transfer From the Stagnation Region of a Circular Cylinder at Re=140?000 -- Conditional Statistics Along Gradient Trajectories in Fluid Turbulence -- Direct Numerical Simulation of Single Gaseous Bubbles in Viscous Liquids -- Wall Heat Load in Unsteady and Pulsating Combustor Flow -- Implicit LES of Passive-Scalar Mixing in a Confined Rectangular-Jet Reactor -- Numerical Simulation of Riblet Controlled Spatial Transition -- Understanding the Dynamics and Control of a Turbulent Impinging Jet via Pulsation and Swirl Using Large Eddy Simulation -- Stability Analysis of a Coupled Helmholtz Resonator with Large Eddy Simulation -- Diffusers with Three-Dimensional Separation as Test Bed for Hybrid LES/RANS Methods -- Final Report on Project GGT0607: Lattice Boltzmann Direct Numerical Simulations of Grid-Generated Turbulence -- Application of FDEM on the Numerical Simulation of Journal Bearings with Turbulence and Inertia Effects -- Numerical Analysis of Transition Effects in 3D Hypersonic Intake Flows -- Preinvestigations of a Redesigned HIRENASD Wing Model in Preparation for New Aero-Structural Dynamic Experiments in ETW -- Transport and Climate -- Modelling Regional Climate Change in Southwest Germany -- Modelling Convection over West Africa -- Miscellaneous Topics -- Molecular Modeling of Hydrogen Bonding Fluids: Vapor-Liquid Coexistence and Interfacial Properties -- Towards a Dynamical Model of Mars’ Evolution -- Computational Considerations for Satellite-Based Geopotential Recovery -- Simulative Analysis of Vehicle-to-X Communication considering Traffic Safety and Efficiency -- Modelling Structural Failure with Finite Element Analysis of Controlled Demolition of Buildings by Explosives Using LS-DYNA.
Includes bibliographical references
Keywords: Hochleistungsrechnen